HUBUNGAN ANTARA JENIS BAHAN BACAAN DAN MINAT BACA DENGAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS XI SMA NEGERI 13 TOMPOBULU KABUPATEN MAROS (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This study aims to determine whether or not there is a relationship between the type of student reading and Indonesian learning outcomes. The Relationship Between Types of Reading Materials and Reading Interest with Indonesian Language Learning Outcomes of Class XI Students of SMA Negeri 13 Tompobulu Maros Regency. The type of research used in this study is correlational using Total Sampling which takes the sample as a whole. Data collection techniques using Checklist questionnaire. After processing the data, the researcher found that the correlation coefficient number in the above results is positive, namely the relationship between X1 with Y is 0.135 and X2 with Y is 0.137, thus it can be interpreted that the more interest in reading is increased according to what students are interested in, the student's Indonesian learning outcomes will also increase.